2023
DOI: 10.3390/diagnostics13162719
|View full text |Cite
|
Sign up to set email alerts
|

Rare Solid Pancreatic Lesions on Cross-Sectional Imaging

Ana Veron Sanchez,
Nuria Santamaria Guinea,
Silvia Cayon Somacarrera
et al.

Abstract: Several solid lesions can be found within the pancreas mainly arising from the exocrine and endocrine pancreatic tissue. Among all pancreatic malignancies, the most common subtype is pancreatic ductal adenocarcinoma (PDAC), to a point that pancreatic cancer and PDAC are used interchangeably. But, in addition to PDAC, and to the other most common and well-known solid lesions, either related to benign conditions, such as pancreatitis, or not so benign, such as pancreatic neuroendocrine neoplasms (pNENs), there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 281 publications
(440 reference statements)
0
3
0
Order By: Relevance
“…Among extrapulmonary sites, TB affecting the gastrointestinal tract is the sixth most common, with abdominal TB accounting for approximately 10% of cases [ 5 , 6 ]. Isolated pancreatic TB is very rare, even in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Among extrapulmonary sites, TB affecting the gastrointestinal tract is the sixth most common, with abdominal TB accounting for approximately 10% of cases [ 5 , 6 ]. Isolated pancreatic TB is very rare, even in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…SPN is more common in young and middle-aged women and is frequently located in the tail of the pancreas ( 41–44 ). Calcification is also a prominent characteristic of SPN ( 45 ). Recently, it was reported that PACC and SPN can be differentiated based on imaging findings (tumour location, maximum diameter, boundary, intratumoral vessels and distant metastasis) ( 42 ).…”
Section: Epidemiology Clinical Features Diagnosis Molecular Features ...mentioning
confidence: 99%
“…Some cases of pNEN show a similar histologic architecture, although necrosis is uncommon ( 46 ). The appearance of pNEN on CT is very variable and includes heterogeneous density with haemorrhage, cystic changes, necrosis and calcification ( 45 , 47 ). In children, PACC needs to be distinguished from pancreatoblastoma, a rare type of malignant pancreatic tumour that arises from the exocrine cells of the pancreas and is rare in adults ( 15 , 16 , 48–50 ).…”
Section: Epidemiology Clinical Features Diagnosis Molecular Features ...mentioning
confidence: 99%